The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11356-022-22815-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mandatory environmental regulation on green development efficiency: evidence from China

Abstract: The existing literature finds that mandatory environmental regulation (MER) can significantly reduce environmental pollution. However, much less is known about how the implementation of MER affects green development efficiency (GDE). Based on the Air Pollution Control Action Plan which was enforced in 2013 in China’s most developed regions as an exogenous shock, we find that first, MER has a significant negative effect on the improvement of GDE by reducing regional scale efficiency. Second, MER mainly reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The “strong” version of the Porter hypothesis is not supported [ 16 ]. Zhan et al proposed that mandatory environmental regulation had a significant negative effect on the improvement of green-development efficiency by changing technical progress [ 17 ]. Lanoie et al provided an empirical analysis, and found that environmental regulation on productivity was negative, while the opposite result was observed with lagged regulatory-variables in Quebec [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The “strong” version of the Porter hypothesis is not supported [ 16 ]. Zhan et al proposed that mandatory environmental regulation had a significant negative effect on the improvement of green-development efficiency by changing technical progress [ 17 ]. Lanoie et al provided an empirical analysis, and found that environmental regulation on productivity was negative, while the opposite result was observed with lagged regulatory-variables in Quebec [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we incorporated both expected and unexpected outputs into the green TFP indicator system. Using the slack-based measure (SBM) directional distance function [ 51 , 52 ] with a nondirectional and variable returns-to-scale model, we measured green TFP using the Malmquist–Luenberge (ML) productivity index ( Eq 1 ): …”
Section: Methodsmentioning
confidence: 99%
“…There are few studies on the relationship between all of them. Although some literature find that technological innovation affects the green development effect of environmental regulation (Zhan et al, 2023), few studies find the role form of technological innovation. Scholars agree that the improvement of innovation level has a positive impact on green development (Ouyang et al, 2020;Ren et al, 2023a).…”
Section: Environmental Regulation Technological Innovation and Green ...mentioning
confidence: 99%
“…Some scholars used the differential method to evaluate the effect of specific policies. For example, they found that the implementation of the Air Pollution Control Action Plan would inhibit the efficiency of green development (Zhan et al, 2023). It can be found that the classification of environmental regulations by pollutants and periods is not common.…”
Section: Measurement Of Environmental Regulationmentioning
confidence: 99%